U.S.-China Relations After Resolution of Taiwan's Status - Cliff, Roger (RAND Corporation, 2007)
Although the question of Taiwan's status may not be resolved soon, considering various outcomes and their possible effects on U.S.-China relations is useful. Ten trajectories for the resolution of Taiwan's status are given, with effects on U.S.-China relations ranging from close cooperation to cold war. As China's military capabilities grow, it will become more difficult but more important to prevent Beijing from trying to use force against Taiwan.